2009
DOI: 10.1002/jmv.21520
|View full text |Cite
|
Sign up to set email alerts
|

Genomic mutations of viral protein 1 and BK virus nephropathy in kidney transplant recipients

Abstract: Genomic variability in the viral protein 1 region of BK polyomavirus (BKV) may change the ability of the virus to replicate. The significance of such changes was studied in clinical samples taken from kidney transplant patients with and without BKV nephropathy. A 94 base-pair fragment of viral protein 1 was amplified from 68 urine, 28 blood, and 12 renal biopsy samples from eight patients with BKV nephropathy, and from 100 urine samples, 17 blood and three renal biopsy samples from 41 of 218 controls. The DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…In these studies, variants were described, but an association with end-organ disease was not always found. In one study, single base-pair mutations were detected more frequently in samples from patients with BK nephropathy, but amino acid changes were randomly distributed in BK nephropathy patients and controls (28). Other studies have identified amino acid changes in the external loops of VP1, which mediate BKV attachment to target cells but did not find an association with viral load or incidence of BK nephropathy (29,30).…”
Section: Discussionmentioning
confidence: 98%
“…In these studies, variants were described, but an association with end-organ disease was not always found. In one study, single base-pair mutations were detected more frequently in samples from patients with BK nephropathy, but amino acid changes were randomly distributed in BK nephropathy patients and controls (28). Other studies have identified amino acid changes in the external loops of VP1, which mediate BKV attachment to target cells but did not find an association with viral load or incidence of BK nephropathy (29,30).…”
Section: Discussionmentioning
confidence: 98%
“…However, it remains to be determined whether even greater variation in MWPyV can be discovered when broader consensus sequence-based assays are used. Others have speculated that sequence variation in BKPyV and JCPyV plays a role in viral pathogenesis and disease severity (4,44). If MWPyV is ultimately found to be a pathogen, it will be interesting to determine whether there are strain-dependent pathogenic phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The main BKV genomic regions depicted as showing sequence divergence are those encoding the VP1 capsid protein and the large T antigen (22,23), while the StAg gene is described as displaying only a few single nucleotide polymorphisms (24). However, despite our assumption that choosing the StAg gene as a PCR target for our in-house PCR would provide a less variable technique for quantification, discrepant BKVL results were observed for some individuals due to mutations at positions G4830A, A4836T, G4876A, and G4877A.…”
Section: Discussionmentioning
confidence: 99%